A nonlinear dynamic finite-element analyses of the basketball-related eye injuries - Karimi, A.; Razaghi, R.; Rahmati, S. M.; Sera, T.; Kudo, S. (Sports Engineering, 2018)
Eye injuries from blunt forces and penetrating objects can cause morbidity, disability, and blindness. Most of these injuries are preventable not only by understanding the detail of injury, but also by portraying the role of the ball`s characteristics. Basketball can induce severe forms of injuries to the eye. This study was aimed at performing a numerical analysis through the fluid-structure interaction on ocular trauma. Balls with different diameters, elastic moduli, and pressures were shot to the eye. Injury in terms of the stresses and deformations in each component of the eye was computed at ~ 0.72 mm deformation in the apex of the cornea. By increasing the diameter of the ball from 20 to 26 cm the stress in the eye components, excluding the aqueous body, vitreous body, and extraconal fat, increased. Stresses of 2.68 and 3.19 MPa were observed in the cornea under the ball diameters of 20 and 26 cm, respectively. Conversely, the elastic modulus and pressure of the ball in the defined range showed no considerable role on the stress in the eye components. The results revealed the importance of the ball size compared to the elastic modulus and pressure in the stress accumulation as a result of ocular trauma.